Clinical and Laboratory Features in Anti-NF155 Autoimmune Nodopathy. Issue 1 (2nd January 2022) - Martín-Aguilar, Lorena; Lleixà, Cinta; Pascual-Goñi, Elba; Caballero-Ávila, Marta; Martínez-Martínez, Laura; Díaz-Manera, Jordi; Rojas-García, Ricard; Cortés-Vicente, Elena; Turon-Sans, Janina; de Luna, Noemi; Suárez-Calvet, Xavier; Gallardo, Eduard; et al.
Abstract : Background and Objectives: To study the clinical and laboratory features of antineurofascin-155 (NF155)–positive autoimmune nodopathy (AN). Methods: Patients with anti-NF155 antibodies detected on routine immunologic testing were included. Clinical characteristics, treatment response, and functional scales (modified Rankin Scale [mRS] and Inflammatory Rasch-built Overall Disability Scale [I-RODS]) were retrospectively collected at baseline and at the follow-up. Autoantibody and neurofilament light (NfL) chain levels were analyzed at baseline and at the follow-up. Results: Forty NF155+ patients with AN were included. Mean age at onset was 42.4 years. Patients presented with a progressive (75%), sensory motor (87.5%), and symmetric distal-predominant weakness in upper (97.2%) and lower extremities (94.5%), with tremor and ataxia (75%). Patients received a median of 3 (2–4) different treatments in 46 months of median follow-up. Response to IV immunoglobulin (86.8%) or steroids (72.2%) was poor in most patients, whereas 77.3% responded to rituximab. HLA-DRB1*15 was detected in 91.3% of patients. IgG4 anti-NF155 antibodies were predominant in all patients; anti-NF155 titers correlated with mRS within the same patient ( r = 0.41, p = 0.004). Serum NfL (sNfL) levels were higher in anti-NF155+ AN than in healthy controls (36.47 vs 7.56 pg/mL, p < 0.001) and correlated with anti-NF155 titers ( r = 0.43, p = 0.001), with I-RODS at baseline ( r = −0.88, p < 0.001) and with maximum I-RODS achieved ( r = −0.58, p = 0.01). Anti-NF155 titers and sNfL levels decreased in all rituximab-treated patients. Discussion: Anti-NF155 AN presents a distinct clinical profile and good response to rituximab. Autoantibody titers and sNfL are useful to monitor disease status in these patients. The use of untagged-NF155 plasmids minimizes the detection of false anti-NF155+ cases. Classification of Evidence: This study provides Class IV evidence that anti-NF155 antibodies associate with a specific phenotype and response to rituximab.